Rural Tourism Entrepreneurship Survey with Emphasis on Eco-museum Concept - Mojgan Ghorbanzadeh (Salehan Institute of Higher Education, 2018)
Unemployment and scarcity of job opportunities count as major problems suffered in villages, especially by the youth. To this end, rural entrepreneurship, particularly in tourism and ecotourism sector, may contribute to the growth of rural economy through strategic and forward-looking planning along with other factors. Innovation and creativity are turning into one of the essential ingredients of continued development. Rural museums, such as “Eco-museum”, are one of the measures taken with regard to protecting various material and spiritual phenomena resulting from traditional habitats. “Eco-museums” can be deemed as a project to support sustainability, and a significant factor for development of entrepreneurship and businesses, especially small- and medium-sized businesses. Espidan, a village in North Khorasan province of Iran, can exert such an effect and play such a role as an eco-museum. Through library resources and field studies, the present study attempts to examine the potentials of Espidan for strengthening its rural tourist properties and fulfilment of ecotouristic objectives in line with three main criteria: public contribution, exclusive eco-museum activities, and creating social, cultural and natural conditions (the determining the vital conditions for a place to evolve into an eco-museum). A study and evaluation of the recommended criteria in Espidan indicates that the village demonstrates considerable potentials for evolving into an eco-museum. As effective steps towards achieving continued development, practical solutions have been proposed for fulfilment of eco-museum objectives as such an evolution into an eco-museum can result in rural entrepreneurship.